Utility of first trimester ultrasound before 12 weeks of gestation at tertiary care centre in western India - Mehta, Shital T.; Yadava, Pushpa A.; Jani, Shashwat K.; Solanki, Tejas V.; Patel, Aastha H.; Mehta, Sweta D.; Shyara, Ashish J.; Rawal, Dhwani R.; Patel, Dhruvi R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: The first trimester begins on the first day of the last menstrual period (LMP) and lasts until the end of 12 weeks of gestation. Transvaginal ultrasound is modality of choice for establishing the presence of an intrauterine pregnancy in the first trimester. The focus of our study is routine early pregnancy ultrasound. The purpose of this study was to diagnose various conditions of pregnancy at an early stage by using ultrasound. Methods: We conducted retrospective data analysis of random 250 pregnant patients who had undergone first-trimester ultrasonography USG) (transvaginal/abdominal) in their first antenatal visit at S.V.P. Hospital, Ahmedabad, Gujarat, India from March 2021 to February 2022. The patient was selected by a simple randomized method. Maternal age, parity, gestational age, and special features regarding maternal gestational history were compared with USG findings. Patients were divided into 13 groups on the basis of ultrasonographic diagnosis. Results: We noted 76.8% of patients had single, viable, intrauterine pregnancies, while 23.2% had complicated pregnancies with uterine anomalies, ovarian cysts, leiomyoma, caesarean scar pregnancy or subchorionic hematomas. Conclusions: Ultrasound measurement of fetus in first trimester is most accurate method to confirm gestational age. It is less expensive and easily available modality. First-trimester ultrasound is useful to define embryonic landmarks in developmental stages with reference to gestational age, early diagnosis of miscarriage, ectopic pregnancy, molar pregnancy, multifetal pregnancy, major fetal malformation. And also, to diagnose pregnancy with leiomyoma, caesarean scar pregnancy, uterine anomaly and pre-eclampsia with the help of uterine artery PI.